Bioremediator effect of filamentous fungi of Citrus x sinensis in soil contaminated with gasoline, Lima-2022 - Cánepa-Carbajal, Angela (2024)
Hydrocarbon contamination is one of the main causes of infertility in areas, leaving very critical levels for the ecosystem, reaching the point of being considered as one of the most concurrent problems due to the uncontrolled management of these by the industrial and productive sector. That is why new strategies have been formulated as a more reliable alternative in situations of response to hydrocarbon spills, with bioremediation with fungi and bacteria being the most efficient strategy. That is why this study aimed to determine the bioremediation effect of filamentous fungi (Aspergillus, Penicillium, Geotrichum, and, Rhizopus) in soil contaminated with 90 octane gasoline (Petroil Gasolina Premium). For this study, 6 kg of soil contaminated with 50 mL, 150 mL and 300 mL of 90 octane gasoline was used, along with four treatments X1 (Penicillium, Geotrichum, and, Rhizopus), X2 (Aspergillus, and, Penicillium), X3 (Penicillium, and, Geotrichum) and X4 (Penicillium), said fungi were isolated from the fruit Citrus x sinensis (L.) Osbeck, 1765 and grown on wheat, rice, CPD and Wheat + Penicillium media respectively. 500 mg of each consortium was inoculated to the treatments and then 250 g of already inoculated contaminated soil was dispersed to form the specimens. At 25 days after inoculation, the final quantity of hydrocarbons in the collected soil was established, determining that the four treatments act as bioremediators, with the average bioremediation of treatment X1 being 43.61%, X2 34.65%, X3 57.23% and X4 55.71%; treatment X3 being the most effective, but X4M3 had the highest percentage of all treatments with 72.06%. Thus, it was concluded that treatment with filamentous fungi Citrus x sinensis does have a bioremedial action in soils contaminated with gasoline.